Milk banks and COVID-19: Scoping review - Alvaro Leon Jacome Orozco; Fabio Alexander Sierra Matamoros; Rossana López Sáleme; Carmen Díaz López; Nubia Castiblanco Lopez; Isabel Rodriguez Hernandez; Doris Amparo Parada Rico (Revista de Nutrición Clínica y Metabolismo, 2020)
To conduct a review of the scope of published information on biosecurity in human milk banks during the COVID-19 pandemic.